Rumors - Van Bommel, Jos (Journal of Finance, 2003)
ABSTRACT A Kyle (1985) model with private information diffusion is used to examine the motivation to spread stock tips. An informed investor with limited investment capacity spreads imprecise rumors to an audience of followers. Followers trade on the advice and move the price. Due to the imprecision of the rumor, the price overshoots with positive probability. This gives the rumormonger the opportunity to trade twice: First when she receives information, then when she knows the price to be overshooting. In equilibrium, rumors are informative and both rumormongers and followers increase their profits at the expense of uninformed liquidity traders.